Dušikov oksid III: zaviralci prekomernega nastajanja - Mravljak, Janez (Farmacevtski vestnik, 2005)
Due to its radical nature nitric oxide can cause many illness and injuries of tissue by elevated concentrations at the site of its excessive formation. NO synthases - family of enzymes that catalyze conversion of arginine to NO and citrulline, are important therapeutic targets at the level of binding of substrate and cofactors as well as at the level of gene expression. Isophormically selective inhibitors of NO synthases represent considerable challenges for drug development.
Keywords: dušikov oksid; inhibitorji; L-arginin; sintaze